Acceleration of cutaneous wound healing by brassinosteroids - Esposito, Debora (2013)
Brassinosteroids are plant growth hormones involved in cell growth, division and differentiation. Their effects in animals are largely unknown, although recent studies showed the anabolic properties of brassinosteroids possibly mediated through the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway. Here we examined biological activity of homobrassinolide (HB) and its synthetic analogues on in vitro proliferation and migration assays in murine fibroblast and primary keratinocyte cell culture. HB stimulated fibroblast proliferation and migration, and weakly induced keratinocyte proliferation in vitro. The effects of topical HB administration on progression of wound closure were further tested in the mouse model of cutaneous wound healing. C57BL/6J mice were given a full thickness dermal wound, and the rate of wound closure was assessed daily for 10 d alongside adenosine receptor agonist CGS-21680 as a positive control. Topical application of brassinosteroid significantly reduced wound size and accelerated wound healing in treated animals. mRNA levels of TGF-β and ICAM-1 were significantly lower, while TNF-α was nearly suppressed in the wounds from treated mice. Our data suggest that topical brassinosteroids accelerate wound healing by positively modulating inflammatory and re-epithelialization phases of the wound-repair process, in partby enhancing Akt signaling in the skin at the edges of the wound and enhancing migration of fibroblasts in a wounded area. Targeting this signaling pathway with brassinosteroids may represent a promising approach to the therapy of delayed wound healing.